COMMUNITY EMPOWERMENT IN THE MANAGEMENT OF NON-COMMUNICABLE DISEASES (DIABETES MELLITUS) IN PLALANGAN SUBDISTRICT, GUNUNGPATI DISTRICT, SEMARANG CITY - Arwani Arwani; Umi Margi Rahayu; Ahmad Riadi; Afifah Salsabila (Wealth Community Empowerment, 2025)
Diabetes mellitus (DM) is a growing global health problem, including in Indonesia where the prevalence continues to rise annually. The management of type 2 diabetes mellitus (T2DM) has largely been health officer-centered, with limited involvement of patients and families, which leads to suboptimal outcomes. This community service program (PkM) aimed to empower communities in Plalangan Subdistrict, Gunungpati District, Semarang City, through the training of health cadres in T2DM management. The program was conducted in two phases: pre-activity coordination with local stakeholders and the implementation of training activities. A total of 40 health cadres participated in training that included education on diabetes management, child diabetes, and simple blood glucose monitoring techniques using glucometers. Results showed that cadres successfully improved their knowledge and practical skills, demonstrated the ability to conduct capillary blood glucose tests, and acted as community educators in DM prevention and management. The involvement of trained cadres strengthened primary healthcare services by supporting early detection, encouraging healthy behaviors, and enhancing patient adherence. This program highlights the critical role of community empowerment and cadre training in improving diabetes management and quality of life at the community level.